Understanding Perceptions of Cultural Landscapes in Europe: A Comparative Analysis Using 'Oppida' Landscapes. (3rd April 2019) - Tully, Gemma; Piai, Chiara; Rodríguez-Hernández, Jesús; Delhommeau, Elodie
ABSTRACT: Climatic, social and demographic change is putting increasing pressure on Europe's cultural landscapes. The European Landscape Convention (ELC) recognises these threats and the need to integrate a wider range of stakeholders in the active management of landscapes in order to negotiate the trade-offs needed for future sustainability. This study explores the complexity of the ELC's aims by analysing stakeholder perceptions and values connected to four European cultural landscapes. Connected by the presence of Late Iron Age oppida, the historic significance of these landscapes is integrated alongside their other ecosystems services in order to make detailed comparisons between approaches to landscapes management in France, Spain and the UK. The analysis highlights conflicts and solutions regarding the unification of heritage, farming, environmental and social needs from the diverse contexts in order to make suggestions for wider best practice in the management of cultural landscapes which align more closely with the integrated stakeholder aims of the ELC.